Desain Aplikasi Penjadwalan Menu Makan Siang Karyawan Menggunakan Pendekatan Design Thinking dan SUS Testing - Fianindra Riezca Augusty; Ryan Putranda Kristianto (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Scheduling is allocating an activity by taking to the sequence of implementation times and availability of limited resources. In the case of employee lunch menus in a company, lunch menu schedule can change every day within a week to adjust the availability of resources limited by company management. Scheduling repeated lunch menus manually will certainly waste a lot of time, an application is needed to do the scheduling automatically. Designing a scheduling application for lunch menus using the Design Thinking approach method applies 5 stages, namely Empathize, Define, Ideate, Prototype, and Testing. Result of this design is an application design which is then evaluated using the System Usability Scale (SUS) to measure user satisfaction. Where user satisfaction data was obtained using the form collecting method using JotForm media which was sent to 30 respondents. The SUS score result is 80.2, which means that the usability design is acceptable or feasible.